Ultra-thin flexible conformal metamaterial absorber and preparation method thereof

By designing an ultra-thin flexible conformal metamaterial absorber, using a combination resonator of hollow ring and cross structure and a flexible polyimide dielectric layer, the problems of poor absorption performance and complex processes in the prior art are solved. It realizes efficient absorption and adaptability of metamaterial absorbers, suitable for complex curved surface equipment and stealth fields.

CN114204273BActive Publication Date: 2024-12-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111534508.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-15
Publication Date
2024-12-27
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

The existing metamaterial absorbers have poor absorption performance under changing polarization angles and large incident angles, and are difficult to adapt to complex curved surface equipment, and the production process is complex, which limits their application in military aircraft and stealth fields.

Method used

Design an ultra-thin flexible conformal metamaterial absorber, consisting of an electromagnetic resonant layer, a dielectric layer and a metal grounding layer, a combination resonator with hollow ring and cross structure, and is heat-pressed with optical transparent adhesive, dielectric The layer is made of a flexible material polyimide, which has a simple structure and is easy to mass production.

Benefits of technology

It realizes efficient absorption of the absorption rate of more than 90% at the four frequencies of the S-band to X-band. It has polarization insensitive and wide-angle incident characteristics. It has ultra-thin structure and strong flexibility and adaptability. It is easy to spread on curved surface equipment and is easy to process. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114204273B_ABST
    Figure CN114204273B_ABST
Patent Text Reader

Abstract

The present invention discloses an ultra-thin flexible conformal metamaterial absorber and a preparation method thereof, which is composed of a periodic array of several unit structures; the unit structure is composed of an electromagnetic resonance layer, a dielectric layer, and a metal grounding layer, the electromagnetic resonance layer is located on the dielectric layer, the dielectric layer is located on the metal grounding layer, and the geometric centers of the electromagnetic resonance layer, the dielectric layer, and the metal grounding layer coincide in the vertical direction; the resonator is composed of a combination of a ring and a cross structure, the cross structure is arranged on the inner side of the ring, and the geometric center of the cross structure coincides with the center of the ring, and the layers are hot-pressed using an optically transparent adhesive. The resonator body is a thin copper plate, and a hollowing process is performed on the thin copper plate to obtain a hollow ring and a hollow cross structure, and the geometric centers of the hollow ring and the hollow cross structure coincide with the geometric center of the thin copper plate. The present invention has very good absorption performance for microwaves from the S band to the X band at four specific frequencies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic microwave metamaterials, and in particular to an ultra-thin flexible conformal metamaterial absorber, which has an absorption rate of more than 90% for microwaves from S band to X band at four frequencies of 3.25 GHz, 6.89 GHz, 9.38 GHz and 10.60 GHz. Background Art

[0002] Microwave usually refers to the frequency of 300MHz (3×10 8 Hz) to 300GHz(3×10 11 Hz), corresponding to an alternating current signal with a wavelength between 1m and 1mm. Its SHF frequency band can be divided into C band (4-8GHz), X band (8-12GHz), Ku band (12-18GHz), and K band (18-26GHz), which are the most widely used bands for radars and various satellites. Microwaves have good maneuverability, a large operating bandwidth, and can transmit more information. They are widely used in communications, satellites, radar antennas and other fields. Electromagnetic microwave absorbers have broad application prospects in today's 5G communications, phased array radars, and electromagnetic stealth due to their efficient absorption of electromagnetic waves in the microwave band.

[0003] Metamaterials refer to artificial composite materials or composite structures with extraordinary physical properties that natural materials do not have. Through human will, metamaterials can be designed from atoms or molecules according to application requirements. They are composite or hybrid material systems with periodic or non-periodic artificial microstructure units arranged through strict and complex artificial design and preparation. Metamaterial absorbers are composed of resonant metamaterials. They mainly use the electromagnetic loss of dielectric materials in metamaterials to convert incident electromagnetic waves into ohmic heat or other forms of energy to achieve electromagnetic wave absorption. Since metamaterial absorbers can achieve near-perfect absorption of incident electromagnetic waves in specific frequency bands through the structural design of functional units, they have become a hot research field in electromagnetic metamaterials. At the same time, due to its extraordinary physical properties, ultra-thin and simple structure, polarization insensitivity and perfect absorption and other absorption characteristics, it has broad application prospects in antenna radar, electromagnetic stealth, sensor technology, thermal imaging, biological detection, photovoltaic cells and other fields. Summary of the invention

[0004] The purpose of the present invention is to provide an ultra-thin flexible conformal metamaterial absorber and a preparation method thereof. The ultra-thin flexible conformal metamaterial absorber has very good absorption performance for microwaves from S band to X band at four specific frequencies, has the characteristics of polarization insensitivity and support for wide-angle incidence, and can maintain good absorption under working environments with changing polarization angles and large incident angles; the ultra-thin flexible conformal characteristics make it easier to cover military aircraft and curved equipment, and has better adaptability to the covering environment; and its simple top-layer resonant structure is easy to process and mass-produce, and has application prospects and markets in the field of stealth.

[0005] The present invention adopts the following technical solutions to achieve the above-mentioned invention objectives:

[0006] An ultra-thin flexible conformal metamaterial absorber is composed of a periodic array of several unit structures; the unit structure is composed of an electromagnetic resonance layer, a dielectric layer, and a metal grounding layer, the electromagnetic resonance layer is located on the dielectric layer, the dielectric layer is located on the metal grounding layer, and the geometric centers of the electromagnetic resonance layer, the dielectric layer, and the metal grounding layer coincide in the vertical direction; the resonator is composed of a combination of a ring and a cross structure, the cross structure is arranged on the inner side of the ring, and the geometric center of the cross structure coincides with the center of the ring.

[0007] Furthermore, the electromagnetic resonance layer, the dielectric layer, and the metal grounding layer are sequentially formed by hot pressing using an optically transparent adhesive.

[0008] Furthermore, the electromagnetic resonance layer is made of copper metal, and its conductivity is 5.8×10 7 S / m.

[0009] Furthermore, the unit period of the electromagnetic resonance layer is 26 mm, and the thickness of the electromagnetic resonance layer is 0.018 mm.

[0010] Furthermore, the resonator body is a thin copper plate, which is hollowed out to obtain a hollow ring and a hollow cross structure, and the geometric centers of the hollow ring and the hollow cross structure coincide with the geometric center of the thin copper plate.

[0011] Furthermore, the inner diameter of the circular ring is 11 mm, and the width of the circular ring is 1.8 mm; the cross structure is a regular cross structure, and the length of a single arm thereof is 13 mm, and the arm width is 2 mm.

[0012] Furthermore, the dielectric layer is made of flexible material polyimide, the dielectric constant is 3, and the loss tangent value of the dielectric is 0.06; the unit period of the dielectric layer is 26 mm, and the layer thickness of the dielectric layer is 0.4 mm.

[0013] Furthermore, the material used for the metal grounding layer is copper, and the electrical conductivity is 5.8×10 7S / m; the thickness of the metal grounding layer is 0.018mm.

[0014] The present invention also discloses a method for preparing an ultra-thin flexible conformal metamaterial absorber, comprising the following steps:

[0015] S1. Mixing: obtaining a polyimide board as a dielectric layer through material mixing;

[0016] S2 impregnation: The prepared polyimide sheet is placed in an organic impregnation solution at a vacuum pressure of 0.05MPa, and then removed and kept in a preheated infrared drying oven for 40 to 60 minutes;

[0017] S3. Cutting: Cut the polyimide sheet into a square sheet of 234 mm × 234 mm, and cut the copper film into a square of 234 mm × 234 mm;

[0018] S4. Hot pressing: The upper and lower copper films and the polyimide plate are pressed together using a hot press for 35 minutes at a temperature of 204°C.

[0019] S5. Grinding plate: Use fine water sandpaper to grind the copper film to remove oxidation and increase the roughness of the copper surface;

[0020] S6. Laminating: Laminating the polyimide plate treated in step S5 with a dry film or wet film to obtain a substrate;

[0021] S7. Exposure: Align the film with the substrate on which the dry film has been pressed. The film pattern is a hollow ring cross. The outer radius of the hollow ring is 11 mm and the width is 1.8 mm. The length of the hollow cross is 13 mm and the width is 2 mm. Transfer the film pattern to the dry film by irradiating with ultraviolet light on an exposure machine.

[0022] S8. Development: The unexposed dry film or wet film is dissolved and washed away by using the weak alkalinity of the developer, and the exposed hollow rings and cross shapes are retained;

[0023] S9. Etching: After the unexposed dry film or wet film is removed by the developer, the copper surface structure in the shape of a ring and a cross is exposed, and the copper surface structure in the shape of a ring and a cross is dissolved and etched away with acid copper chloride to obtain the desired hollow surface structure;

[0024] S10. Stripping: Peel off the exposed dry film or wet film with sodium hydroxide solution to reveal the hollow pattern.

[0025] The present invention has the following beneficial effects:

[0026] The ultra-thin, flexible, conformal, quad-band metamaterial absorber of the present invention achieves nearly perfect high-efficiency absorption at four frequencies of 3.25 GHz, 6.89 GHz, 9.38 GHz and 10.60 GHz, with absorption rates all exceeding 90%.

[0027] It has the characteristics of being ultra-thin, with a total structural thickness of only 0.436mm, which is 0.0047 of the wavelength at the lowest absorption frequency.

[0028] The resonant layer has a simple top-layer resonant structure, and the resonant layer composed of a hollow ring and a hollow cross structure is easy to process and mass-produce.

[0029] It has polarization insensitivity and wide-angle characteristics in transverse electric (TE) and transverse magnetic (TM) modes. Different polarization angles have little effect on the absorption performance; the overall absorption rate decreases with the increase of the incident angle, and still maintains an absorption rate of more than 80% when the incident angle reaches 40°.

[0030] It has the function of flexible conformal. Using ultra-thin flexible material polyimide as the dielectric layer, the metamaterial absorber can be bent and folded to a certain extent, and has better adaptability to the covering environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 An exploded diagram of the unit structure of an ultra-thin flexible conformal metamaterial absorber according to the present invention;

[0032] Figure 2 This is a schematic diagram of the electromagnetic resonance layer structure of an ultra-thin flexible conformal metamaterial absorber according to the present invention;

[0033] Figure 3 A schematic diagram of the flexible and conformal ultra-thin flexible conformal metamaterial absorber according to the present invention;

[0034] Figure 4 A schematic diagram of the boundary setting of an ultra-thin flexible conformal metamaterial absorber according to the present invention;

[0035] Figure 5 This is an absorption spectrum diagram of an ultra-thin flexible conformal metamaterial absorber in TE and TM modes according to the present invention;

[0036] Figure 6 It is a comparative absorption spectrum diagram of a combined electromagnetic resonator, a single hollow ring structure and a single hollow cross structure of an ultra-thin flexible conformal metamaterial absorber according to the present invention;

[0037] Figure 7 It is an absorption spectrum diagram of an ultra-thin flexible conformal metamaterial absorber of the present invention at different polarization angles in TE and TM modes;

[0038] Figure 8 It is an absorption spectrum diagram of an ultra-thin flexible conformal metamaterial absorber described in the present invention at different incident angles in TE and TM modes;

[0039] Fig. 9 This is an electric field distribution diagram of the electromagnetic resonance layer of an ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 3.25 GHz;

[0040] Fig.10 This is an electric field distribution diagram of the electromagnetic resonance layer of an ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 6.89 GHz;

[0041] Fig.11 This is an electric field distribution diagram of the electromagnetic resonance layer of an ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 9.38 GHz;

[0042] Fig.12 This is an electric field distribution diagram of the electromagnetic resonance layer of an ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 10.60 GHz;

[0043] Fig.13 This is a current distribution diagram of the electromagnetic resonance layer and the ground metal layer of the ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 3.25 GHz;

[0044] Fig.14 This is a current distribution diagram of the electromagnetic resonance layer and the ground metal layer of the ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 6.89 GHz;

[0045] Fig.15 This is a current distribution diagram of the electromagnetic resonance layer and the ground metal layer of the ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 9.38 GHz;

[0046] Fig.16 This is a current distribution diagram of the electromagnetic resonance layer and the ground metal layer of the ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 10.60 GHz;

[0047] Fig.17 This is a magnetic field distribution diagram of the dielectric layer of an ultra-thin flexible conformal metamaterial absorber according to the present invention at an absorption frequency of 3.25 GHz;

[0048] Fig.18 This is a magnetic field distribution diagram of the dielectric layer of an ultra-thin flexible conformal metamaterial absorber described in the present invention at an absorption frequency of 6.89 GHz;

[0049] Fig.19This is a magnetic field distribution diagram of the dielectric layer of an ultra-thin flexible conformal metamaterial absorber according to the present invention at an absorption frequency of 9.38 GHz;

[0050] Fig. 20 This is a magnetic field distribution diagram of the dielectric layer of an ultra-thin flexible conformal metamaterial absorber according to the present invention at an absorption frequency of 10.60 GHz;

[0051] Fig.21 The effect of the unit period (side length) of the ultra-thin flexible conformal metamaterial absorber described in the present invention on the absorption performance;

[0052] Fig. 22 The effect of the hollow cross arm length of the electromagnetic resonator of the ultra-thin flexible conformal metamaterial absorber described in the present invention on the absorption performance;

[0053] Fig.23 The effect of the inner diameter of the hollow ring of the electromagnetic resonator of the ultra-thin flexible conformal metamaterial absorber described in the present invention on the absorption performance;

[0054] Fig.24 The invention discloses an effect of dielectric layer thickness on absorption performance of an ultra-thin flexible conformal metamaterial absorber. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments:

[0056] like Figure 1 As shown, this embodiment is an ultra-thin flexible conformal metamaterial absorber, which is composed of a periodic array of several unit structures, wherein the unit structure is composed of an electromagnetic resonance layer 1, a dielectric layer 2, and a metal grounding layer 3, the electromagnetic resonance layer 1 is located on the dielectric layer 2, the dielectric layer 2 is located on the metal grounding layer 3, and the geometric centers of the electromagnetic resonance layer 1, the dielectric layer 2, and the metal grounding layer 3 coincide in the vertical direction.

[0057] The electromagnetic resonance layer 1, the dielectric layer 2, and the metal grounding layer 3 are sequentially formed by hot pressing using an optically transparent adhesive.

[0058] The electromagnetic resonance layer 1 is made of copper metal, and its conductivity is 5.8×10 7 The unit period (side length) of the electromagnetic resonance layer 1 is 26 mm, that is, the length and width are both 26 mm, and the thickness of the electromagnetic resonance layer 1 is 0.018 mm.

[0059] The dielectric layer 2 is made of flexible polyimide (PI), with a dielectric constant of 3 and a loss tangent of 0.06. The unit period (side length) of the dielectric layer 2 is 26 mm, that is, the length and width are both 26 mm; the thickness of the dielectric layer 2 is 0.4 mm.

[0060] The material used for the metal grounding layer 3 is copper, and the conductivity is 5.8×10 7 The unit period (side length) of the metal grounding layer 3 is 26 mm, that is, the length and width are both 26 mm, and the layer thickness of the metal grounding layer 3 is 0.018 mm.

[0061] like Figure 2 As shown, the resonator is composed of a ring and a cross structure. The cross structure is arranged inside the ring, and the geometric center of the cross structure coincides with the center of the ring. The inner diameter of the ring is 11mm, and the width of the ring is 1.8mm; the cross structure is a regular cross structure, and its single-side arm length is 13mm and the arm width is 2mm.

[0062] The resonator body is a thin copper plate, which is hollowed out to obtain a hollow ring and a hollow cross structure, and the geometric centers of the hollow ring and the hollow cross structure coincide with the geometric center of the thin copper plate.

[0063] The ultra-thin flexible conformal metamaterial absorber is formed by a periodic array of unit structures, which are arranged in N×N in two-dimensional directions, where N is a positive integer.

[0064] The following describes a method for preparing the ultra-thin flexible conformal metamaterial absorber according to this embodiment, comprising the following steps:

[0065] (1) Ingredients: Through material ratio, an FR4 board with electromagnetic parameters close to those of the materials used in simulation is obtained.

[0066] (2) Impregnation: Place the prepared FR4 board in an organic impregnation solution with a vacuum pressure of 0.05 MPa, take it out and keep it in a preheated infrared drying oven for 40 to 60 minutes.

[0067] (3) Cutting: Use a kraft paper cutter and a copper foil cutter to cut the FR board and copper film into square sheets of 260 mm × 260 mm respectively.

[0068] (4) Hot pressing: Use a hot press to press the copper film and FR4 board together for 35 minutes at a temperature of 204°C.

[0069] (5) Grinding: Use fine sandpaper to carefully grind the copper plate to remove oxidation and increase the roughness of the copper surface to facilitate film adhesion.

[0070] (6) Film pasting: The processed substrate is pasted with a dry film or a wet film by hot pressing or coating for subsequent exposure production.

[0071] (7) Exposure: Align the film with the substrate on which the dry film has been pressed, and use ultraviolet light on the exposure machine to transfer the film pattern to the photosensitive dry film.

[0072] (8) Development: The unexposed dry film / wet film is dissolved and washed away using the weak alkalinity of the developer (sodium carbonate), while the exposed part is retained.

[0073] (9) Etching: After the unexposed dry film / wet film is removed by the developer, the copper surface will be exposed. Acidic copper chloride is used to dissolve and corrode this exposed copper surface to obtain the desired surface structure.

[0074] (10) Film stripping: Use sodium hydroxide solution to peel off the exposed dry film protecting the copper surface to reveal the surface structure pattern.

[0075] The following introduces the simulation calculation of the ultra-thin flexible conformal metamaterial absorber of this embodiment:

[0076] The electromagnetic calculation software CST STUDIO SUITE (CST) is used for simulation calculation. The software uses finite integration technology to divide the structure into grids and applies Maxwell equations and boundary conditions to each grid for electromagnetic calculation. The calculation domain boundary of the absorbing unit is set as follows Figure 3 As shown. The incident wave source is a plane electromagnetic wave, incident along the z direction, and the incident wave vector is k; the electric field vector E is parallel to the x direction, and the magnetic field vector H is parallel to the y direction. In the x and y directions, the boundary is set to the unit period Unit cell, and in the z direction, the boundary is set to the open boundary Open. In this way, the entire boundary appears as a Floquet periodic boundary, which can simulate the absorption effect after simulating the absorbing unit array.

[0077] The absorption performance of the ultra-thin flexible conformal quad-band metamaterial absorber of the present invention can be expressed by the absorption coefficient A(ω), which can be derived from the reflectivity R(ω) and the transmittance T(ω) as follows: A(ω)=1-R(ω)-T(ω), R(ω) and T(ω) can be expressed by scattering parameters (S parameters), R(ω)=|S 11 | 2 ,T(ω)=|S 21 | 2 Since the thickness of the bottom copper layer is greater than the skin depth of the copper material for the incident electromagnetic wave, the electromagnetic wave cannot be transmitted from the bottom layer to the outside, so T(ω) can be considered to be 0. Therefore, the absorption rate A(ω) can be simplified to A(ω)=1-R(ω)=1-|S 11 | 2 .

[0078] The absorption spectrum of the ultra-thin flexible conformal quad-band metamaterial absorber of the present invention is as follows: Figure 4As shown in the figure, it can have four highly efficient absorption peaks in the 0-12GHz band, with absorption frequencies of 3.25GHz, 6.89GHz, 9.38GHz and 10.60GHz, and the absorption rate is more than 90%. In the TE and TM modes, the absorption frequency and absorption rate of the ultra-thin flexible conformal four-band metamaterial absorber remain basically unchanged, which reflects its insensitivity to TE and TM polarized waves.

[0079] The combined electromagnetic resonance structure of the ultra-thin flexible conformal quad-band metamaterial absorber of the present invention is split into separate hollow rings and hollow crosses to better analyze the influence of the resonance structure on the absorption performance. Figure 5 As shown, a single hollow ring resonator produces two absorption peaks at low frequencies and has little effect on high-frequency absorption; while a single hollow cross resonator mainly affects high-frequency absorption and has little effect on low-frequency absorption.

[0080] The absorption performance of the ultra-thin flexible conformal quad-band metamaterial absorber at different polarization angles and incident angles is as follows: Figure 6 and 7 As shown. Figure 6 As shown in FIG. 1 , the absorption spectrum does not change substantially with the change of the polarization angle, whether in the TE or TM mode. This is because the four-fold rotational symmetry structure of the ultra-thin flexible absorber makes it polarization-insensitive. Figure 7 As shown in the figure, in the TE mode, as the incident angle increases, the absorption frequency and absorption rate of the first and second peaks remain basically unchanged; the second absorption peak gradually splits into two absorption peaks, the original peak absorption rate remains unchanged, the absorption rate first decreases and then increases, and the newly formed peak has an obvious red shift as the incident angle increases, and the absorption rate also increases accordingly; the fourth absorption peak has an absorption frequency that remains unchanged at first, then produces a blue shift, and the absorption rate gradually decreases as the incident angle increases. With the increase of the incident angle, the absorption peaks show a trend of gradually increasing, and the absorption frequency also remains above 80%. In the TM mode, with the increase of the incident angle, the absorption frequency of the four absorption peaks changes little, and the absorption rate gradually decreases. When the incident angle reaches 40°, the lowest absorption rate remains at about 80%. Such results show that in the TE and TM modes, the ultra-thin flexible absorber absorbs electromagnetic waves with large incident angles.

[0081] The electric field, current and magnetic field distribution of the ultra-thin flexible conformal quad-band metamaterial absorber of the present invention are given by Figure 9-19 As shown. Figure 9-12As shown in the figure, at the low-frequency absorption point, the electric field of the electromagnetic resonance layer is mainly distributed on the inner and outer sides of the hollow circular ring, and partly on the inner and outer sides of the hollow cross structure; while at the high-frequency absorption point, the electric field of the electromagnetic resonance layer is mainly distributed on the outer side of the inner cross, and partly on the inner side of the outer circular ring. The electric field distribution causes the flow of charges to form surface currents. Figure 12-15 As shown in the figure, the distribution of the surface current of the electromagnetic resonance layer is consistent with the electric field distribution. The low-frequency absorption points are concentrated on both sides of the hollow ring, and the high-frequency absorption points are concentrated on both sides of the hollow cross. Due to the polarization of the dielectric layer, the electric field of the grounding layer presents a distribution opposite to that of the top layer, which makes the current in the bottom layer completely opposite to that in the top layer. A pair of antiparallel currents in the electromagnetic resonance layer and the metal grounding layer can be equivalent to a pair of magnetic dipoles, thereby generating magnetic resonance in the dielectric layer and consuming the energy of the incident electromagnetic wave. Figure 16-19 As shown. Therefore, at the low-frequency absorption point, the absorption of the incident electromagnetic wave by the ultra-thin flexible absorber is mainly due to the combined effect of the electric resonance occurring at the outer hollow ring of the electromagnetic resonance layer and the magnetic resonance occurring in the corresponding dielectric layer; while at the high-frequency absorption point, the absorption of the electromagnetic wave by the absorber is mainly achieved by the combined effect of the electric resonance occurring at the inner hollow cross of the electromagnetic resonance layer and the magnetic resonance occurring in the corresponding dielectric layer. This is consistent with the absorption law of the single hollow ring and cross structure, which is caused by the sub-wavelength characteristics of the metamaterial absorber. The wavelength of the incident electromagnetic wave at low frequency is longer, and the structure of the absorber that undergoes electromagnetic resonance should be increased accordingly. Therefore, absorption at low frequency occurs at the hollow ring with a larger structural size, while absorption at high frequency occurs at the hollow cross structure with a relatively smaller structural size.

[0082] The influence of the geometric structure size of the ultra-thin flexible conformal quad-band metamaterial absorber of the present invention on the absorption performance is as follows Figure 20-23 Since the absorption frequency and absorption rate of the flexible ultra-thin absorber can be adjusted by changing the size of the geometric structure parameters, the influence of the main geometric structure parameters on the absorption performance of the flexible ultra-thin absorber is analyzed. Fig. 20 As shown in Figure 2, the increase in the period (side length) of the absorbing structure unit leads to an obvious red shift in the second frequency band. Fig.21 As shown in Figure 2, as the length of the hollow cross structure increases, the first and third bands are red-shifted, while the second and fourth bands remain basically unchanged. Fig. 22 As shown in Figure 2, as the inner diameter of the hollow ring increases, all absorption peaks undergo red shifts to varying degrees. Fig.23As shown in the figure, the thickness of the polyimide dielectric layer has a great influence on the absorption performance of the absorber. As the thickness of the dielectric layer increases, the first and second frequency bands will blue shift, and the third and fourth frequency bands will red shift. The absorption rate of the absorption band increases with the thickness of the dielectric layer. In summary, the first and third absorption bands are mainly affected by the length of the hollow cross structure and the inner diameter of the hollow ring, the second absorption band is mainly affected by the period of the absorber structure unit, the fourth absorption band is mainly affected by the inner diameter of the hollow ring, and the thickness of the dielectric layer has an impact on all absorption bands.

[0083] In summary, the ultra-thin flexible conformal quad-band metamaterial absorber described in the present invention is designed based on polyimide (PI), a dielectric material of a flexible circuit board. The top resonator is a combination of a hollow ring and a cross, and the thickness is only 0.436 mm. It obtains 4 absorption peaks with an absorption rate higher than 90% from the S band to the X band, has polarization-insensitive absorption characteristics, and maintains an ideal absorption effect for incident waves with large incident angles in both TE and TM modes. This design scheme achieves efficient absorption in the microwave band, and its structural characteristics such as ultra-thin flexibility and simple resonant structure make it easy to mass produce and commercialize. It has broad application prospects in the fields of electromagnetic shielding of curved structures, meteorological satellites, and radar detection, and has guiding significance for the design of other flexible absorbers.

[0084] The above specifically describes the preferred implementation of the present invention. Of course, the present invention can also take a form different from the above-mentioned implementation mode. Equivalent changes or corresponding modifications made by technicians familiar with the field without violating the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. An ultra-thin flexible conformal metamaterial absorber, characterized in that: The invention is composed of a periodic array of several unit structures; the unit structure is composed of an electromagnetic resonance layer, a dielectric layer, and a metal grounding layer, the electromagnetic resonance layer is located on the dielectric layer, the dielectric layer is located on the metal grounding layer, and the geometric centers of the electromagnetic resonance layer, the dielectric layer, and the metal grounding layer coincide with each other in the vertical direction; the resonator is composed of a ring and a cross structure, the cross structure is arranged on the inner side of the ring, and the geometric center of the cross structure coincides with the center of the ring; the electromagnetic resonance layer, the dielectric layer, and the metal grounding layer are formed by hot pressing using an optically transparent adhesive in sequence; the electromagnetic resonance layer is made of copper metal with a conductivity of 5.8×10 7 S / m; the unit period of the electromagnetic resonance layer is 26mm, and the thickness of the electromagnetic resonance layer is 0.018mm; the resonator body is a thin copper plate, and the thin copper plate is hollowed out to obtain a hollow ring and a hollow cross structure, and the geometric centers of the hollow ring and the hollow cross structure coincide with the geometric center of the thin copper plate; the inner diameter of the ring is 11mm, and the width of the ring is 1.8mm; the cross structure is a regular cross structure, and its single-side arm length is 13mm and the arm width is 2mm; the dielectric layer adopts flexible material polyimide, the dielectric constant is 3, and the loss tangent value of the medium is 0.06; the unit period of the dielectric layer is 26mm, and the thickness of the dielectric layer is 0.4mm; the material used for the metal grounding layer is metal copper, and the conductivity is 5.8×10 7 S / m; the unit period of the metal grounding layer is 26 mm, and the layer thickness of the metal grounding layer is 0.018 mm.

2. The method for preparing an ultra-thin flexible conformal metamaterial absorber according to claim 1, characterized in that: The steps include: S1. Mixing: obtaining a polyimide board as a dielectric layer through material mixing; S2 impregnation: The prepared polyimide sheet is placed in an organic impregnation solution at a vacuum pressure of 0.05MPa, and then removed and kept in a preheated infrared drying oven for 40 to 60 minutes; S3. Cutting: Cut the polyimide sheet into a square sheet of 234 mm × 234 mm, and cut the copper film into a square of 234 mm × 234 mm; S4. Hot pressing: The upper and lower copper films and the polyimide plate are pressed together using a hot press for 35 minutes at a temperature of 204°C. S5. Grinding plate: Use fine water sandpaper to grind the copper film to remove oxidation and increase the roughness of the copper surface; S6. Laminating: Laminating the polyimide plate treated in step S5 with a dry film or wet film to obtain a substrate; S7. Exposure: Align the film with the substrate on which the dry film has been pressed. The film pattern is a hollow ring cross. The outer radius of the hollow ring is 11 mm and the width is 1.8 mm. The length of the hollow cross is 13 mm and the width is 2 mm. Using ultraviolet light on an exposure machine, the negative pattern is transferred to the dry film; S8. Development: The unexposed dry film or wet film is dissolved and washed away by using the weak alkalinity of the developer, and the exposed hollow rings and cross shapes are retained; S9. Etching: After the unexposed dry film or wet film is removed by the developer, the copper surface structure in the shape of a ring and a cross is exposed, and the copper surface structure in the shape of a ring and a cross is dissolved and etched away with acid copper chloride to obtain the desired hollow surface structure; S10. Stripping: Peel off the exposed dry film or wet film with sodium hydroxide solution to reveal the hollow pattern.